Buku Digital Berbasis Scrapbook Terhadap Literasi Baca Tulis Siswa Kelas III SD - Kadek Mita Lasmini; Ni Ketut Suarni; I Wayan Widiana (Journal for Lesson and Learning Studies, 2022)
In understanding a reading, students have not been able to capture and pour ideas into good writing. The purpose of this study is to analyze scrapbook-based digital books on literacy. This type of research is a quasi-experimental research using a nonequivalent post-test only control group design. The population of this study amounted to 105 third grade elementary school students. The sample of this research is 58 students. The method used to collect data is a test. The data collection instrument used test questions. The data analysis technique used is descriptive statistical analysis and inferential statistics. The result of the analysis is that the calculated F value for the Levenge test is 1.227 with a probability of 0.273 because the probability is > 0.05, so H1 is rejected. The t-value is 6.340 and the significant value is 0.000 <0.05. So there is a significant difference between the average post test scores in the experimental class and the control class. It was concluded that scrapbook-based digital books could improve students' reading and writing literacy.